Implementation of Presidential Regulation Number 87 of 2017 about Strengthening Student’s Character Education - Putra, Ismail Danka; Anggraini, Dian Tri (PPSDP International Journal of Education, 2023)
The purpose of this study is to describe and analyze the implementation of Presidential Regulation Number 87 of 2017 concerning strengthening student character education at SMA Negeri 3 Kayuagung, Ogan Komering Ilir Regency, as well as the enabling and impeding factors for the implementation of that regulation at Kayuagung 3 Public High School, Ogan Komering Ilir Regen. This study is qualitative in nature. The study’s findings indicate that: 1) internal communication at SMA Negeri 3 Kayuagung, as well as communication with the school’s supervisor and committee and other connected agencies, all happened as planned; 2) There is already a clear standard operating procedure (SOP), and the majority of policy implementers are familiar with its procedures; 3) All policy implementers have a high commitment to the implementation of Presidential Regulation No. 87 of 2017 concerning Strengthening Character Education, which is not all teachers’ ability to apply character education to the subjects they teach.